The Prevalance of Anti-Hepatitis C Virus in Patients with Hepatocellular Carcinoma - Gürhan KADIKÖYLÜ; Vedat GÖRAL; Halil DEĞERTEKİN and Mine TURHANOĞLU and Eralp ARIKAN and Fikri CANORUÇ (Turkish Journal of Gastroenterology, 2020)
-